KEPEMIMPINAN AHAB DALAM 1 RAJA-RAJA 21: 1-16 DALAM PERSPEKTIF HANNAH ARENDT TENTANG BANALITAS KEJAHATAN - Jhon Ferdinand Sihombing (Manna Rafflesia, 2023)
Leadership is something that everyone should have. Good leadership will bring oneself or others towards the best goals. Not infrequently those who are called leaders actually make their people miserable. Make position as an opportunity to fulfill their heart's desire. Ahab is an example of a leader who does not protect his people, but allows the law to be manipulated for his pleasure. Methods or prevention are needed so that Ahab's form of leadership does not recur. This paper aims to explore Ahab's Leadership in Hannah Arendt's Perspective on the Banality of Evil by using qualitative methods and a library study approach. Through this paper, it can be concluded that Ahab is the perpetrator of the banality of evil because of ideology, shallow thinking and blind obedience. In Hannah Arendt's thought, everyone must think and critically evaluate all things that are inside and outside of human beings.